Determinasi Potensi Penghasil Pajak Daerah dan Retribusi Daerah dengan Pendekatan Overlay (Studi Kasus Pada Pemerintah Kabupaten Balangan) - Rijjal, brilliant Adin; Dirgantari, Novi (Politeknik Ganesha Medan, 2024)
One of the regions in Indonesia that is facing the threat of a regional financial drought in the future is South Kalimantan Province. 50% of the region depends on income from coal mining which is estimated to only be available until 2030. The aim of this research is to determine the types of regional taxes and levies that have potential for regional original income. The data analysis method is overlay analysis through three stages, namely growth analysis, contribution analysis and classification analysis of types of regional taxes. The results of this research are (1) analysis of the growth of most types of regional taxes in Balangan Regency including unsuccessful criteria. (2) analysis of the contribution of most types of regional taxes in Balangan Regency to local revenue includes very poor criteria. (3) Overlay analysis of the classification of potential regional taxes for Balangan Regency for 2021-2022 shows that the type of tax included in the developing category is advertising. Conclusion There are no types of taxes included in the prime category, there are no potential taxes, only advertising tax is developing. Meanwhile, the types of taxes that fall into the underdeveloped category include hotel taxes, restaurant taxes, catering/catering services taxes and the like, taxes on massage parlors, reflexology, steam baths/spas, and fitness centers, street lighting taxes, parking taxes, taxes swallow's nest, ground water tax, tax on non-metallic minerals and other rocks, PBB P2 (Rural and Urban Land and Building Tax), and BPHTB-Transfer of Rights tax means that the ratio of growth and contribution to the average tax is small. The results of the overlay analysis calculation show that most types of regional taxes in Balangan Regency are identified as developing and underdeveloped